2021
DOI: 10.1182/blood.2020008600
|View full text |Cite
|
Sign up to set email alerts
|

When non-Whiteness becomes a condition

Abstract: The term "benign ethnic neutropenia" describes the phenotype of having an ANC less than 1500 cells/uL with no increased risk of infection. This is most commonly seen in those of African ancestry. In addition, ANC ranges from countries in Africa emphasize that ANC levels below 1500 cell/uL are common and harmless. The lower ANC levels are driven by the Duffy null [Fy(a-b-)] phenotype which is protective against malaria and seen in 80-100% of those of Sub-Saharan African ancestry and <1% of those of Cauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 28 publications
1
56
0
1
Order By: Relevance
“…The findings of this study are consistent with those of Gari et al [10] who also reported a high prevalence (20%) of neutropenia in Jeddah. Several other studies have shown a variable frequency of neutropenia among different populations [9,[13][14][15]. Moreover, the findings of this study indicated that the 2.5 th percentile of neutrophil count was lower than what is accepted now as lower end of the reference range;1.5 × 10 9 /L, in all seven cities.…”
Section: Discussionsupporting
confidence: 41%
“…The findings of this study are consistent with those of Gari et al [10] who also reported a high prevalence (20%) of neutropenia in Jeddah. Several other studies have shown a variable frequency of neutropenia among different populations [9,[13][14][15]. Moreover, the findings of this study indicated that the 2.5 th percentile of neutrophil count was lower than what is accepted now as lower end of the reference range;1.5 × 10 9 /L, in all seven cities.…”
Section: Discussionsupporting
confidence: 41%
“…44 colonial-era slave trade has resulted in a majority of African Americans carrying the Duffy-null variant. This ancestryinformative marker has been identified as the cause of the clinically inconsequential pattern of benign ethnic neutropenia, [63][64][65] which causes African Americans to have a lower average circulating white blood cell count compared with White Americans. It has also been proposed that Duffy-null status be considered in monitoring blood counts in patients with breast cancer receiving treatments associated with neutropenia.…”
mentioning
confidence: 99%
“…As recently demonstrated by Merz and colleagues, the number of neutrophils in individuals with BEN is perfectly adequate for host defence, so it should be considered a normal variant and not a "condition" or "disease" [23]. Duffy antigen phenotyping or ACKR1 gene sequencing is considered gold standard for identifying BEN, but this procedure is not currently performed in either of the study sites.…”
Section: Determining Ben In the Cnrd Cohortmentioning
confidence: 99%
“…Nevertheless, our method is consistent with existing literature and may possibly even enhance our findings if BEN prevalence is higher when patients from a wider demographic are included. Ideally, future studies should look at pharmacogenetic testing to identify the ACKR1 genotype (rs2814778 C-C allele SNP) opposed to selfdeclared ethnicity when screening for BEN [3,23,45,46] especially considering that studies have demonstrated a weak correlation between skin colour or selfdeclared race and genetic ancestry [47]. While diagnostic agreement between haematologists was very good in our study, the investigational emphasis relies on excluding other putative causes for neutropenia, and entails timeconsuming, laborious and expensive tests, to make a diagnosis of exclusion, for essentially a non-pathogenic ethnic variation in normality.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation